Wheat trade - does Russia price discriminate across export destinations? - Zsombor Pall; Oleksandr Perekhozhuk; Ramona Teuber; Thomas Glauben (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Significant changes have taken place on the world wheat market over the last decade. Russia, a former net wheat importer has become a leading exporter with a world market share of 13.8 percent in 2009/2010. Though there are several studies on the pricing behaviour of Canadian and US wheat exporters, there is none on the pricing behaviour of Russian wheat exporters. The present paper tries to fill this lack of research by providing a quantitative analysis of the pricing behaviour of Russian wheat exporters. We employ a pricing-to-market (PTM) model on annual Russian wheat export data, covering the period 2002-2009 and 22 export destinations. Our findings indicate that Russian wheat exporters behave rather competitively and exercise pricing to market behaviour only in five export destinations.
Keywords: L13; Q17; 330; Russia; wheat export; international trade; pricing to market